Taṭbīqu Ṭarīqah al-Istijābah al-Badaniyyah al-Kulliyyah fī Fahmi "Mufradāt al-Afʿāl" fī Mādati Tamrīn al-Lugah al-‘Arabiyyah li al-Șaff al-Awwal - Rahmawati, Fitra Awalia; Oktaviana, Nanda Mia; Nurlaila, Riza (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
The research aims to determine the influence of the Total Physical Response method on understanding the vocabulary of verb forms (af'al) in the Tamrin Lughah lessons for grade 1. This research was conducted at Darussalam Gontor for Girls campus 2. The Research methodology used in this study is a quantitative approach, specifically the experimental posttest-only control design. The population study in this research consisted of first-year students at the Islamic Teacher Training College. The sample employed simple random sampling and was divided into two groups: an experimental group of 55 students and a control group of 55 students. Data were collected through oral tests and written documents to gather student numbers, and data analysis methods, including the t-test, were used. The findings indicate that the t-value in the table corresponds to 1.98 at a 5% significance level and to 2.63 at a 1% significance level. The researcher determined that the calculated t-value is smaller than the t-value in the table: (1.98 > 1.28 < 2.63). Therefore, the hypothesis stating that there are no effects of the Total Physical Response method on understanding verb vocabulary in the first-year language practice material at the Darussalam Gontor Girls' Institute, Campus 2, is invalid. This suggests that teachers should pay more attention to students' language skills, and students should focus on teacher explanations during language lessons.